Pop city : Korean popular culture and the selling of place (2018)
Most Korean1 television dramas end with a still screen image, designed to act as a cliff-hanger to each episode. The tension is left to linger for a while; then the credits start to run, accompanied by background music against the still screen frame, revealing the names of the drama series sponsors one by one. Since the mid-2000s, the names of Korean municipalities have started appearing in the first few credits, implying that they are the production’s biggest sponsors. My inquiry into cities’ drama sponsorships began with a very brief discovery of one small city’s name in the list of fast-rolling credits of a 2006 megabudget historical drama. Initially, like most other viewers, I did not notice or pay much attention to the credit lists.